Preparation of a preservative for the preservation of red blood cells and their antigens - موسى , اماره; سوزان الشمالي ,; راما ابراهيم , (Latakia University Journal -Medical Sciences Series, 2023)
Blood transfusion is the most common treatment for anemia in thalassemia, sickle cell anemia and oncology patients, but it has many immunological and non-immunological complications. Alloimmunization is one of the most important immunological complications, as it causes a Hemolytic Transfusion Reaction (HTR) and Hemolytic Disease of the Fetus and Newborn (HDFN). It also increases the difficulty in securing adequate blood. It is prevented by alloantibodies screening before each blood transfusion. In this study, we aim to prepare a preservative in house that maintain red blood cells and their antigens to be the basis for designing the local panels for future implementation in antibodies screening and identification without importing them from abroad at very high costs. Venous blood samples were collected from 10 different donors, their red cells carry the following antigens: D, E, e, C, c, K and Fya to test the ability of the prepared preservative Tishreen Hospital. PH testing, bacterial culture, erythrocyte lysis and effectiveness of the erythrocyte antigens prepared in preservative were also performed. According to our results, we can use this preservative to maintain the local panel at least 3 months.